Lower Success Rate of Débridement and Implant Retention in Late Acute versus Early Acute Periprosthetic Joint Infection Caused by Staphylococcus spp. Results from a Matched Cohort Study. Issue 6 (June 2020) - Wouthuyzen-Bakker, Marjan; Sebillotte, Marine; Huotari, Kaisa; Escudero Sánchez, Rosa; Benavent, Eva; Parvizi, Javad; Fernandez-Sampedro, Marta; Barbero, José Maria; Garcia-Cañete, Joaquín; Trebse, Rihard; Del Toro, Maria; Diaz-Brito, Vicens; et al.
Abstract: Background: Surgical débridement, antibiotics and implant retention (DAIR) is currently recommended by international guidelines for both early acute (postsurgical) and late acute (hematogenous) periprosthetic joint infections (PJIs). However, due to a different pathogenesis of infection, a different treatment strategy may be needed. Questions/purposes: (1) Compared with early acute PJIs, are late acute PJIs associated with a higher risk of DAIR failure? (2) When stratified by microorganism, is the higher risk of failure in late acute PJI associated with Staphylocococcus aureus infection? (3) When analyzing patients with S. aureus infection, what factors are independently associated with DAIR failure? Methods: In this multicenter observational study, early acute and late acute PJIs treated with DAIR were retrospectively evaluated and matched according to treating center, year of diagnosis, and infection-causing microorganism. If multiple matches were available, the early acute PJI diagnosed closest to the late acute PJI was selected. A total of 132 pairs were included. Treatment success was defined as a retained implant during follow-up without the need for antibiotic suppressive therapy. Results: Late acute PJIs had a lower treatment success (46% [60 of 132]) compared with early acute PJIs (76% [100 of 132]), OR 3.9 [95% CI 2.3 to 6.6]; p < 0.001), but the lower treatment success of late acute PJIs was only observed when caused by Staphylococcus spp ( S. aureus : 34% versus 75%; p < 0.001; coagulase-negative staphylococci: 46% versus 88%; p = 0.013, respectively). On multivariable analysis, late acute PJI was the only independent factor associated with an unsuccessful DAIR when caused by S. aureus (OR 4.52 [95% CI 1.79 to 11.41]; p < 0.001). Conclusions: Although DAIR seems to be a successful therapeutic strategy in the management of early acute PJI, its use in late acute PJI should be reconsidered when caused by Staphylococcus spp. Our results advocate the importance of isolating the causative microorganism before surgery. Level of Evidence: Level III, therapeutic study.